P-005 Last-Recorded P2Y12 Reaction Units Value Predicts Thromboembolic and Haemorrhagic Complications Occurring up to 6 Months after Treatment in Patients with Cerebral Aneurysms Treated with the Pipeline Embolisation Device. (14th July 2013) - Almandoz, J Delgado; Crandall, B; Fease, J; Scholz, J; Anderson, R; Kadkhodayan, Y; Tubman, D
Abstract : Background and Purpose: A recent study identified a pre-procedure P2Y12 reaction units (PRU) value <60 or >240 as a strong independent predictor of perioperative thromboembolic and haemorrhagic complications occurring up to 30 days after treatment of cerebral aneurysms with the Pipeline Embolisation Device (PED). This study aims to determine if a last-recorded PRU value <60 or >240 predicts thromboembolic and haemorrhagic complications occurring up to 6 months after treatment of cerebral aneurysms with the PED in the same patient cohort. Methods: We recorded patient and aneurysm characteristics, P2Y12 receptor antagonist administered, PRU value with VerifyNow, procedural variables, number of P2Y12 receptor antagonist dose adjustments, and thromboembolic and haemorrhagic complications occurring up to 6 months after PED procedures at our institution during an 8-month period. Complications causing a permanent disabling neurological deficit or death were considered major. Multivariate regression analysis was performed to identify independent predictors of thromboembolic and haemorrhagic complications. Target P2Y12 receptor inhibition range was initially 80–200 PRU and was subsequently expanded to 60–240 PRU. Results: Forty-four patients underwent 48 PED procedures at our institution during the study period. There were 11 thromboembolic and haemorrhagic complications occurring up to 6 months after treatment in our cohort (22.9%), 5 of which were major (10.4%). Among the 5 major complications, 4 occurred in the perioperative period and 1 occurred on post-operative day 50 (ICH with subdural extension contralateral to the PED in a patient with autopsy-proven amyloid angiopathy). Four of the 5 major complications occurred in patients who exhibited markedly elevated (292) or decreased (0, 10, 58) PRU values shortly before or at the time of the complication. A last-recorded PRU value <60 or >240 was the only independent predictor of all (p-value 0.002) and major (p-value 0.03) thromboembolic and haemorrhagic complications in our cohort (Table). Most patients (71%) required, on average, 2 adjustments to the dose or type of P2Y12 receptor antagonist administered to remain within the 60–240 target PRU range. Conclusion: In our cohort, a last-recorded PRU value <60 or 240> was the only independent predictor of all and major thromboembolic and haemorrhagic complications up to 6 months after PED procedures. Disclosures: J. Delgado Almandoz: 2; C; Covidien/ev3. B. Crandall: 2; C; Covidien/ev3. J. Fease: None. J. Scholz: None. R. Anderson: None. Y. Kadkhodayan: None. D. Tubman: 2; C; Covidien/ev3, MicroVention.